Text-to-Braille Translator in a Chip - Zhang, Xuan; Ortega-Sanchez, Cesar (Murdoch University, 2006)
This paper describes the hardware implementation of a text to Braille Translator using Field-Programmable Gate Arrays (FPGAs). Different from most commercial software-based translators, the circuit presented in this paper is able to carry out text-to-Braille translation in hardware. The translator is based on the translating algorithm, proposed by Paul Blenkhorn [1]. The Very high speed Hardware Description Language (VHDL) was used to describe the chip in a hierarchical way. The test results indicate that the hardware-based translator achieves the same results as software-based commercial translators, with superior throughput.